Penilaian Efektivitas Biostimulan terhadap Pertumbuhan, Hasil dan Kualitas Tomat di Kondisi Lahan Terbuka - Permata Ika Hidayati; As'ad Syamsul Arifin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This study conducted "C" Block-Farm, Petungsewu Kecamatan WAgir Kabupaten Malang during the period of 2022-2023, explores the impact of biostimulants oon the growth, yield, and quality of tomatoes. The primary objectives include investigating the significant effects of biostimulants and determining the optimal stage for their application, given the current emphasis on sustainable farming practices. THe experimental design employed randomized Blick Design (RBD) with three replications and eight treatments. Results indicate that biostimulant application particularly as a foliar spray, significantly enhances crop growth and stimulates reproductive growth in later stages compared to control plants.